2006
DOI: 10.1007/s10620-005-9019-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Receptor Antagonist (LU-135252) Improves the Microcirculation and Course of TNBS Colitis in Rats

Abstract: The role of microcirculation in the pathogenesis and course of chronic inflammatory bowel disease is still unclear. The aim of this study was the evaluation of the role of microcirculation in colitis activity in the rat TNBS (trinitrobenzenesulfonic acid) colitis model using endothelin-1 and a selective endothelin-1 receptor antagonist (LU-135252). Target parameters were capillary blood flow, functional capillary density, vascular permeability, and leukocyte sticking as well as recording of hematocrit, weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…While this may be the first demonstration of enhanced hypoxia in a T-cell transfer model of colitis, previous reports indicate that the inflammatory response to rectal installation of TNBS also induces elevations in colonic hypoxia (3, 4), and also reduces capillary density and mucosal blood flow (11–13). In contrast to our T-cell transfer model, enhanced hypoxia with TNBS is not likely related to hematocrit, with the TNBS-induced increase in hematocrit speculated to be due to a fluid shift out of the circulation due to increased vascular permeability (12).…”
Section: Discussionmentioning
confidence: 67%
“…While this may be the first demonstration of enhanced hypoxia in a T-cell transfer model of colitis, previous reports indicate that the inflammatory response to rectal installation of TNBS also induces elevations in colonic hypoxia (3, 4), and also reduces capillary density and mucosal blood flow (11–13). In contrast to our T-cell transfer model, enhanced hypoxia with TNBS is not likely related to hematocrit, with the TNBS-induced increase in hematocrit speculated to be due to a fluid shift out of the circulation due to increased vascular permeability (12).…”
Section: Discussionmentioning
confidence: 67%
“…ET‐1 causes vasoconstriction through ET A receptors located on vascular smooth muscle cells and results in microcirculatory disturbances of the colon . Accordingly, ET receptor blockade has been shown to improve the gastrointestinal microcirculation in inflammatory diseases, most probably by interrupting the ET‐1/ET A receptor interaction . ET‐1, however, may also act vasodilatory by binding to ET B receptors .…”
Section: Discussionmentioning
confidence: 99%
“…Buhr and colleagues (7,(21)(22)(23), using intravital microscopy, have repeatedly observed an increased mucosal blood flow within 24 h after induction of colitis with TNBS and a reduced blood flow after 3 days. Deniz et al (6) recorded decreased arterial mesenteric blood flow at early stages in TNBS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of colonic mucosal blood flow is poorly understood, and its importance during colonic injury is still unclear. Studies in recent years have yielded contradictory data, showing either an increased (8,11,14,27) or a decreased (7,11,21,22,38) blood flow in different animal models of colitis, using a variety of measuring techniques. The few blood flow studies conducted in humans with IBD have indicated that the mucosal blood flow is increased in inflamed regions (3,15).…”
mentioning
confidence: 99%